Féerie pour un scandale : l’art et la morale dans Lolita (1958) de Vladimir Nabokov - Jacques Sohier (Revue LISA)
The moral apotheosis of the narrator-character Humbert Humbert consists in the narrative of transgressive acts like pedophilia and incest. How is it possible for the writer first, and then the reader, to reconcile art and morality ? In the preface to Lolita, V. Nabokov impersonates the fictive John Ray and looks at transgression with both a moral and clinical intent. In the postface to the novel written by V. Nabokov himself, the writer affirms his aesthetics and claims that his novel has no moral in tow. A close reading of this preface shows a writer on the defensive in the face of a persisting scandal. Poetical options are carefully explained to the reader. Thus aesthetic bliss comes foremost transcending moralism. Nabokov shows himself a rigorous formalist insisting on the purity of art and its disconnection from ethics. A dialectic defending perversion causes the reader to shake in his/her moral foundation. The specious reasoning of the narrator makes Lolita a masterpiece of casuistry. Lolita creates a utopia beyond good and evil where the freedom of the reader can find in the sanctuary of art the proper place to exercise itself.